Dewaxing powder and preparation method thereof
By using specific ratio aggregates and additives in the wax discharge powder, a wax discharge powder with a porous structure and high SiO2 content is prepared, which solves the problems of wax discharge powder adhesion and penetration, and improves the wax respiration ability and pore stability. The properties reduce the reaction with the ceramic matrix and ensure the stability of product performance.
Patent Information
- Application Number
- CN202411355946.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, wax discharge powder is prone to adhere and penetrate into the porous ceramic matrix, resulting in product color differences, powder loss, hole blockage and reduced smoke.
The ratio of aggregate, inorganic binder, organic binder, pore-forming agent, dispersing agent, suspension agent and water is used to prepare a porous structure wax discharge powder. The mass fraction of SiO2 is greater than or equal to 85%, less than or equal to 98. %, to reduce the reaction with the ceramic matrix, and to adapt ceramic atomized cores of different pore sizes by adjusting the particle size and content of the pore-forming agent.
The porous structure and high SiO2 content of wax discharge powder are achieved, which reduces adhesion and penetration problems, improves wax respiration ability and pore stability, reduces the reaction between wax discharge powder and ceramic matrix, and avoids the influence of product performance.
Smart Images

Figure CN119390434A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wax removal powder, and in particular to wax removal powder and a preparation method thereof. Background Art
[0002] Ceramic atomizer core is a component that can atomize the e-liquid when powered on, formed by a series of processes such as thick film printing, sintering, and assembly based on porous ceramics. At present, the porous ceramic matrix production process used in the atomizer core industry is mostly hot die casting. The main process of this process is wax slurry production, molding, wax removal, and high-temperature sintering. The high-quality porous ceramic matrix of the atomizer core needs to have a porous structure and sufficient structural strength. Therefore, a large amount of paraffin, beeswax, stearic acid, pore-forming agent, glass powder and other substances are often added in the wax slurry production process of porous ceramics. The addition of the above substances makes it extremely easy for the product to stick to the powder during the wax removal stage, and the wax removal powder to penetrate into the porous ceramic matrix along the porous channels.
[0003] The adhesion of the wax powder not only causes the product to have a different color after high-temperature sintering, but also may cause further powder loss during the assembly and use of the atomizer core, affecting product performance. The penetration of the wax powder will cause the holes to be blocked, affecting the oil conduction, and ultimately causing a decrease in the amount of smoke or a burnt smell during the inhalation process. Summary of the invention
[0004] The present application provides a wax removal powder and a preparation method thereof, so as to solve the problems of wax removal powder adhesion and wax removal powder clogging the holes of an atomizing core in the prior art.
[0005] A first aspect of an embodiment of the present application provides a wax-removing powder, wherein the raw materials for preparing the wax-removing powder include aggregate, additives and water, the additives include inorganic binder, organic binder, pore-forming agent, dispersant and suspending agent, and the ratio of the raw materials includes: aggregate, with a mass percentage greater than or equal to 60% and less than or equal to 80%; the aggregate contains quartz powder; the inorganic binder, with a mass percentage greater than or equal to 0 and less than or equal to 5%; the organic binder, with a mass percentage greater than or equal to 0.5% and less than or equal to 2%; the pore-forming agent, with a mass percentage greater than or equal to 0 and less than or equal to 20%; the dispersant, with a mass percentage greater than 0 and less than or equal to 0.5%; the suspending agent, with a mass percentage greater than or equal to 0 and less than or equal to 0.5%; and water, with a mass percentage greater than or equal to 10% and less than or equal to 25%.
[0006] According to one embodiment of the present application, atomizer core waste and / or talc.
[0007] According to one embodiment of the present application, the mass percentage of quartz powder in the aggregate is greater than or equal to 70% and less than or equal to 85%, the mass percentage of atomization core waste in the aggregate is greater than or equal to 10% and less than or equal to 20%, and the mass percentage of talc in the aggregate is greater than or equal to 5% and less than or equal to 10%.
[0008] According to one embodiment of the present application, the mass percentage of SiO2 in quartz powder is greater than or equal to 97% and less than 100%; the mass percentage of SiO2 in atomization core waste is greater than or equal to 80% and less than or equal to 90%; the mass percentage of SiO2 in talc is greater than or equal to 60% and less than or equal to 65%.
[0009] According to one embodiment of the present application, the median particle size of the aggregate is in the range of 10 μm to 20 μm.
[0010] According to an embodiment of the present application, the inorganic binder includes glass powder and / or feldspar.
[0011] According to one embodiment of the present application, the inorganic binder includes at least potassium oxide and sodium oxide, wherein the mass fraction of potassium oxide and sodium oxide in the wax removal powder is less than or equal to 1%.
[0012] According to one embodiment of the present application, the median particle size of the inorganic binder is in the range of 1 μm to 5 μm.
[0013] According to one embodiment of the present application, the softening point temperature of the inorganic binder is 1200°C to 1250°C.
[0014] According to one embodiment of the present application, the mesh size range of the sieve used for sieving the wax powder is 80 mesh to 200 mesh.
[0015] According to one embodiment of the present application, the organic binder includes polyvinyl alcohol and / or hydroxypropyl methylcellulose; the pore-forming agent includes at least one of polymethyl methacrylate, graphite powder and walnut sand; the median particle size range of the pore-forming agent is 1 μm to 10 μm; the dispersant includes at least one of sodium humate, PC67 and polyacrylic acid amine; and the suspending agent includes carboxymethyl cellulose.
[0016] According to one embodiment of the present application, the wax-removing powder has a porous structure, and the porosity of the wax-removing powder is 30% to 50%.
[0017] According to one embodiment of the present application, in the wax removal powder, the mass fraction of SiO2 is greater than or equal to 85% and less than or equal to 98%.
[0018] The second aspect of the embodiment of the present application provides a method for preparing wax removal powder, which is used to prepare any of the above wax removal powders, including: preparing a slurry to be used with the raw materials for preparing the wax removal powder; spray granulating the slurry to be used to obtain a first intermediate product; screening the first intermediate product once to obtain a second intermediate product; calcining the second intermediate product to obtain a third intermediate product; and screening the third intermediate product twice to obtain wax removal powder.
[0019] According to one embodiment of the present application, preparing the stand-by slurry includes: mixing an organic binder, a suspending agent and water to obtain a first mixed liquid, and stirring the first mixed liquid for 10 hours to 15 hours, then adding a dispersant to obtain a second mixed liquid, and stirring the second mixed liquid for 5 hours to 7 hours, then adding an aggregate and an inorganic binder to obtain a third mixed liquid, adding the third mixed liquid to a ball mill and ball milling for 5 hours to 10 hours to obtain a fourth mixed liquid, adding a pore-forming agent to the fourth mixed liquid and continuing to ball mill for 2 hours to 4 hours to obtain the stand-by slurry.
[0020] According to one embodiment of the present application, the step of spray granulating the slurry to be used to obtain the first intermediate product includes: placing the slurry to be used in a centrifugal spray tower, the inlet air temperature of the centrifugal spray tower is 210°C to 220°C, the outlet temperature is 100°C to 110°C, the feed frequency is 25Hz to 30Hz, and the centrifugal speed is 20Hz to 30Hz.
[0021] According to one embodiment of the present application, the step of screening the first intermediate product once to obtain the second intermediate product includes: using a screening machine to screen the first intermediate product to obtain the second intermediate product; the mesh number range of the sieve used for screening the second intermediate product is 60 mesh to 200 mesh.
[0022] According to one embodiment of the present application, in the step of calcining the second intermediate product to obtain the third intermediate product, the calcination temperature is 1250°C to 1350°C.
[0023] According to one embodiment of the present application, the step of performing secondary screening on the third intermediate product to obtain wax removal powder includes: using a screening machine to screen the third intermediate product to obtain wax removal powder; the mesh number range of the sieve used for sieving the wax removal powder is 80 mesh to 200 mesh.
[0024] The beneficial effects are as follows: the raw materials for preparing the wax removal powder disclosed in the present application include aggregate, additives and water, and the additives include inorganic binders, organic binders, pore formers, dispersants and suspending agents. The wax removal powder obtained in the implementation mode of the present application is a porous structure, which ensures a strong wax absorption capacity; and in the wax removal powder, the mass fraction of SiO2 is greater than or equal to 85% and less than or equal to 98%, and the inertia is high, which can reduce the reaction between the wax removal powder and the porous ceramic matrix, thereby reducing the problem of wax removal and powder sticking; the particle size of the wax removal powder is adjustable, so that the wax removal powder particles can be adjusted according to the pore size of the porous ceramic matrix to solve the problem of penetration and pore blocking. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:
[0026] Figure 1 This is a schematic diagram of a screening process provided in an embodiment of the present application;
[0027] Figure 2 It is a schematic diagram of secondary screening provided in an embodiment of the present application;
[0028] Figure 3 This is a schematic diagram of the size change provided in the embodiment of the present application.
[0029] Figure 4 It is a schematic diagram of wax removal powder provided in an embodiment of the present application;
[0030] Figure 5 It is a schematic diagram of wax removal powder provided in the comparative example of this application. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0032] It should be noted that the terms "first" and "second" in this application are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first" and "second" can explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.
[0033] The present application provides a wax-removing powder, wherein the raw materials for preparing the wax-removing powder include aggregate, additives and water, wherein the additives include inorganic binder, organic binder, pore-forming agent, dispersant and suspending agent, and the proportion of the raw materials includes: aggregate, with a mass percentage greater than or equal to 60% and less than or equal to 80%; the aggregate contains quartz powder; the inorganic binder, with a mass percentage greater than or equal to 0 and less than or equal to 5%; the organic binder, with a mass percentage greater than or equal to 0.5% and less than or equal to 2%; the pore-forming agent, with a mass percentage greater than or equal to 0 and less than or equal to 20%; the dispersant, with a mass percentage greater than or equal to 0 and less than or equal to 0.5%; the suspending agent, with a mass percentage greater than or equal to 0 and less than or equal to 0.5%; and water, with a mass percentage greater than or equal to 10% and less than or equal to 25%.
[0034] Specifically, in the embodiment of the present application, the raw materials for preparing the wax removal powder include aggregate, inorganic binder, organic binder, pore former, dispersant, suspending agent and water. Among them, the aggregate contains quartz powder, which has the characteristics of high inertness, can avoid the reaction of the prepared wax removal powder with the porous ceramic matrix, and reduce the problem of wax removal sticking powder. The inorganic binder adopts a material with a high softening point and low potassium and low sodium content, which well guarantees the stability of the pores of the wax removal powder during the production process, and also avoids the wax removal powder deterioration caused by potassium and sodium precipitation or re-melting during the repeated use of the wax removal powder. By adjusting the ratio of the organic binder and the suspending agent, wax removal powders with different viscosities and different particle morphologies can be produced, which can adapt to the wax removal of ceramic atomization cores with different structures. The role of the pore former is to obtain a wax removal powder with a porous structure. By adjusting the particle size and content of the pore former, wax removal powders with different pore sizes can also be produced to adapt to the wax removal of different atomization cores.
[0035] It should be noted that the aggregate includes quartz powder. Quartz powder is a substance with a high silicon content. The aggregate with a high SiO2 content formed by quartz powder has high inertness, which can reduce the reaction between the wax removal powder and the ceramic atomization core matrix and reduce the problem of wax removal powder sticking.
[0036] According to one embodiment of the present application, the aggregate further includes atomization core waste and / or talc.
[0037] Specifically, the atomizer core waste and / or talc are also high-silicon content materials. The aggregate contains quartz powder and atomizer core waste and / or talc, which can increase the silicon content of the wax removal powder to a certain extent. It has high inertness, can reduce the reaction between the wax removal powder and the ceramic atomizer core matrix, and reduce the problem of wax removal powder sticking.
[0038] According to one embodiment of the present application, the mass percentage of quartz powder in the aggregate is greater than or equal to 70% and less than or equal to 85%, the mass percentage of atomization core waste in the aggregate is greater than or equal to 10% and less than or equal to 20%, and the mass percentage of talc in the aggregate is greater than or equal to 5% and less than or equal to 10%.
[0039] Specifically, quartz powder, atomizer core waste and talc are all high-silicon content materials. The high-SiO2 content aggregate formed by quartz powder and / or atomizer core waste and / or talc has high inertness, which can reduce the reaction between wax removal powder and ceramic atomizer core matrix and reduce the problem of wax removal powder sticking.
[0040] The mass percentage of quartz powder in the aggregate can be 70%, 72%, 75%, 78%, 81%, 83%, 85%, etc., or a range consisting of any two of the above values, such as 70%-78%, 78%-85%, 72%-81%, 75%-85%, etc.
[0041] The mass percentage of atomizer core waste in the aggregate can be 10%, 12%, 14%, 15.5%, 17.8%, 18.6%, 19%, 20%, etc., or a range consisting of any two of the above values, such as 10% to 15.5%, 15.5% to 20%, 12% to 17.8%, 14% to 18.6%, etc.
[0042] The mass percentage of talc in the aggregate can be 5%, 5.5%, 6%, 7%, 8.5%, 9.2%, 10%, etc., or a range consisting of any two of the above values, such as 5%-7%, 7%-10%, 5.5%-8.5%, 7%-9.2%, etc.
[0043] According to one embodiment of the present application, the mass percentage of SiO2 in quartz powder is greater than or equal to 97% and less than 100%; the mass percentage of SiO2 in atomization core waste is greater than or equal to 80% and less than or equal to 90%; the mass percentage of SiO2 in talc is greater than or equal to 60% and less than or equal to 65%.
[0044] In the implementation manner of the present application, the content of SiO2 in the aggregate material is relatively high. The high content of SiO2 makes the aggregate highly inert, which can reduce the reaction between the wax removal powder and the ceramic atomization core matrix and reduce the problem of wax removal powder sticking.
[0045] According to one embodiment of the present application, the median particle size D50 of the aggregate is in the range of 10 μm to 20 μm.
[0046] Specifically, the median particle size D50 of the aggregate can be 10 μm, 11 μm, 12.5 μm, 15 μm, 16.8 μm, 18 μm, 18.9 μm, 20 μm, etc., or a range consisting of any two of the above values, such as 10 μm to 15 μm, 15 μm to 20 μm, 12.5 μm to 18.9 μm, 16.8 μm to 20 μm, etc. The median particle size D50 of the aggregate can better control the pore size and porosity of the wax removal powder within the above range.
[0047] It should be noted that the components of the aggregate are quartz powder, or the components of the aggregate are quartz powder and at least one of atomization core waste and talc, and the median particle size D50 of the quartz powder, atomization core waste and talc are all in the range of 10μm to 20μm.
[0048] According to an embodiment of the present application, the inorganic binder includes glass powder and / or feldspar.
[0049] Among them, the glass powder and / or feldspar are mainly composed of main components such as albite and potassium feldspar.
[0050] According to one embodiment of the present application, the inorganic binder includes at least potassium oxide (K2O) and sodium oxide (Na2O), wherein the mass fraction of potassium oxide (K2O) and sodium oxide (Na2O) in the wax removal powder is less than or equal to 1%.
[0051] Specifically, the inorganic binder includes glass powder and / or feldspar, and the glass powder and / or feldspar are mainly composed of main components such as sodium feldspar and potassium feldspar. Therefore, the inorganic binder includes at least K2O and Na2O, wherein the mass fraction of K2O and Na2O in the wax removal powder is less than or equal to 1%. If the content of K2O and Na2O is greater than the above range, K2O and Na2O will form a eutectic body with other materials at high temperature, which will reduce the viscosity of the final wax removal powder, thereby reducing the wax removal effect of the wax removal powder. If the content of K2O and Na2O is high, it is easy to volatilize and cause the wax removal powder to deteriorate. This embodiment controls the mass fraction of K2O and Na2O in the wax removal powder to be less than or equal to 1%, and the viscosity of the final wax removal powder is relatively high, and the wax removal powder is prevented from deteriorating due to the precipitation or re-melting of potassium and sodium during repeated use.
[0052] According to one embodiment of the present application, the median particle size D50 of the inorganic binder is in the range of 1 μm to 5 μm.
[0053] Specifically, the median particle size D50 of the inorganic binder can be 1μm, 1.1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.6μm, 4.5μm, 5μm, etc., or a range consisting of any two of the above values, for example, 1μm~2.5μm, 2.5μm~5μm, 1.5μm~3.6μm, 2.5μm~4.5μm, etc.
[0054] The median particle size D50 of the inorganic binder within the above range makes the wax removal powder more dispersible.
[0055] It should be noted that the components constituting the inorganic binder are glass powder and / or feldspar, and the median particle size D50 of the glass powder and / or feldspar is in the range of 1 μm to 5 μm respectively.
[0056] According to one embodiment of the present application, the softening point temperature of the inorganic binder is 1200°C to 1250°C.
[0057] The softening point temperature refers to the temperature at which the inorganic binder changes from solid to liquid. If the softening point temperature of the inorganic binder is lower than the above range, the wax removal powder and the atomization core base will be bonded. The softening point temperature of the inorganic binder can be 1200°C, 1210°C, 1222°C, 1231°C, 1238°C, 1240°C, 1245°C, 1250°C, etc., or a range consisting of any two of the above values, such as 1200°C to 1231°C, 1231°C to 1250°C, 1210°C to 1238°C, 1222°C to 1240°C, etc. The inorganic binder adopts a high softening point temperature, which greatly improves the stability of the pores of the wax removal powder during the production process.
[0058] According to one embodiment of the present application, the mesh size range of the sieve used for sieving the wax powder is 80 mesh to 200 mesh.
[0059] Among them, when the mesh number of the sieve is 200 meshes, the particle size of the wax removal powder is about 74μm, and when the mesh number of the sieve is 80 meshes, the particle size of the wax removal powder is about 187.5μm. The particle size range of the wax removal powder is 74μm to 187.5μm. The particle size of the wax removal powder is within the above range, which can be adapted to the wax removal of ceramic atomization cores with different structures and solve the problem of penetration and pore blockage.
[0060] According to one embodiment of the present application, the organic binder includes polyvinyl alcohol (PVA) and / or hydroxypropyl methylcellulose (HPMC).
[0061] According to one embodiment of the present application, the pore-forming agent includes at least one of polymethyl methacrylate (PMMA), graphite powder and walnut sand.
[0062] According to one embodiment of the present application, the median particle size D50 of the pore former is in the range of 1 μm to 10 μm.
[0063] The median particle size D50 of the pore-forming agent can be 1 μm, 1.5 μm, 2 μm, 2.6 μm, 5 μm, 5.6 μm, 6.2 μm, 8 μm, 9.2 μm, 10 μm, etc., or a range consisting of any two of the above values, such as 1 μm to 5 μm, 5 μm to 10 μm, 2 μm to 8 μm, 2.6 μm to 9.2 μm, etc. By adjusting the particle size and amount of the pore-forming agent, wax-removing powders with different pore sizes can be produced to adapt to the wax removal of different atomization cores. It is not easy to form through holes when the particle size is smaller than the above range, and it is easy to cause the pore-forming agent to separate and separate in the subsequent spray granulation process when the particle size is larger than the above range.
[0064] According to one embodiment of the present application, the dispersant includes at least one of sodium humate, PC67 and polyacrylic acid amine. Among them, PC67 is a dispersant of ZIMA Chemical, which has stronger dispersing and degumming properties, can effectively improve production efficiency and improve the quality of wax removal powder.
[0065] According to one embodiment of the present application, the suspending agent includes carboxymethyl cellulose (CMC).
[0066] According to one embodiment of the present application, the wax-removing powder has a porous structure, and the porosity of the wax-removing powder is 30% to 50%.
[0067] The porous structure ensures that the wax removal powder has a strong wax absorption ability. The porosity of the wax removal powder can be 30%, 35%, 38%, 40%, 42%, 46%, 48%, 50%, etc., or a range composed of any two of the above values, such as 30%-40%, 40%-50%, 35%-46%, 38%-48%, etc.
[0068] According to one embodiment of the present application, in the wax removal powder, the mass fraction of SiO2 is greater than or equal to 85% and less than or equal to 98%. The mass percentage of SiO2 in the wax removal powder is greater than or equal to 85% and less than or equal to 98%. The SiO2 content is high and has high inertness, which can reduce the reaction between the wax removal powder and the ceramic atomization core matrix and reduce the problem of wax removal powder sticking. The mass percentage of SiO2 in the wax removal powder can be 85%, 87.5%, 89%, 90%, 92%, 95.5%, 98%, etc., or a range composed of any two of the above values, such as 85% to 90%, 90% to 97%, 87.5% to 95.5%, 92% to 98%, etc.
[0069] The second aspect of the present application provides a method for preparing wax removal powder, which is used to prepare any of the above wax removal powders, including: preparing a slurry to be used with the raw materials for preparing the wax removal powder; spray granulating the slurry to be used to obtain a first intermediate product; screening the first intermediate product once to obtain a second intermediate product; calcining the second intermediate product to obtain a third intermediate product; and screening the third intermediate product twice to obtain wax removal powder.
[0070] The specific method for preparing the wax removal powder comprises:
[0071] (1) Prepare the slurry to be used.
[0072] An organic binder, a suspending agent and water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 10 to 15 hours, a dispersant is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 to 7 hours, an aggregate and an inorganic binder are added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 5 to 10 hours to obtain a fourth mixed solution, a pore-forming agent is added to the fourth mixed solution and ball-milled for 2 to 4 hours to obtain a slurry to be used.
[0073] (2) The slurry to be used is subjected to spray granulation to obtain a first intermediate product.
[0074] The slurry to be used is placed in a centrifugal spray tower, the inlet air temperature of the centrifugal spray tower is 210°C to 220°C, the outlet temperature is 100°C to 110°C, the feed frequency is 25Hz to 30Hz, and the centrifugal speed is 20Hz to 30Hz.
[0075] (3)Reference Figure 1 , the first intermediate product is screened once to obtain a second intermediate product.
[0076] The first intermediate product is screened by a screening machine to obtain a second intermediate product, wherein the mesh number of the screen used for screening the second intermediate product ranges from 60 mesh to 200 mesh, or the particle size of the second intermediate product ranges from 74 μm to 250 μm.
[0077] (4) calcining the second intermediate product to obtain a third intermediate product.
[0078] The calcination temperature is 1250°C to 1350°C.
[0079] (5)Reference Figure 2 , the third intermediate product is screened for the second time to obtain wax removal powder.
[0080] The third intermediate product is screened by a screening machine to obtain wax removal powder; the mesh number of the sieve used for screening the wax removal powder ranges from 80 meshes to 200 meshes.
[0081] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0082] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0083] Embodiment 1:
[0084] (1) Preparation of slurry for use: 1% by weight of PVA and 18.5% by weight of water were mixed to obtain a first mixed solution, and after stirring the first mixed solution for 15 hours, 0.5% of sodium humate was added to obtain a second mixed solution, and after stirring the second mixed solution for 5 hours, aggregate (65% quartz, 8% atomization core waste, 4% talcum powder) and 1% glass powder were added to obtain a third mixed solution, and the third mixed solution was added to a ball mill for ball milling for 10 hours to obtain a fourth mixed solution, and 2% PMMA was added to the fourth mixed solution and continued to be ball milled for 2 hours to obtain a slurry for use.
[0085] (2) Granulation spraying: The slurry to be used is placed in a centrifugal spray tower with an inlet temperature of 210°C, an outlet temperature of 100°C, a feed frequency of 25 Hz, and a centrifugal speed of 20 Hz. After obtaining the first intermediate product,
[0086] (3) Primary screening: The first intermediate product is screened by a screening machine to obtain a second intermediate product. The mesh size of the second intermediate product is in the range of 60 to 200 mesh. For details, refer to Figure 3 One sieving step.
[0087] (4) Calcination: The second intermediate product is calcined at a temperature of 1250° C. to obtain a third intermediate product.
[0088] (5) Secondary screening: The third intermediate product is screened by a screening machine to obtain wax-removing powder. The mesh size of the wax-removing powder is in the range of 80 to 200 meshes. For details, refer to Figure 4 Secondary screening step.
[0089] Example 2
[0090] Similar to Example 1, except that:
[0091] The preparation of the stand-by slurry in step (1) of Example 1 is adjusted as follows: 1% by mass of PVA, 0.4% by mass of CMC, and 22.5% by mass of water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 15 hours, 0.1% PC67 is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 hours, aggregate (56% quartz, 16% atomization core waste, 4% talcum powder) is added to obtain a third mixed solution, and the third mixed solution is added to a ball mill and ball-milled for 10 hours to obtain a stand-by slurry.
[0092] Example 3
[0093] Similar to Example 1, except that:
[0094] The preparation of the stand-by slurry in step (1) of Example 1 is adjusted as follows: 0.5% by mass of HPMC and 17% by mass of water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 15 hours, 0.5% of polyacrylic acid amine is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 hours, aggregate (56% quartz, 8% atomization core waste, 8% talcum powder) and 5% of glass powder are added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 10 hours to obtain a fourth mixed solution, 5% of PMMA is added to the fourth mixed solution, and the ball-milling is continued for 2 hours to obtain the stand-by slurry.
[0095] Example 4
[0096] Similar to Example 1, except that:
[0097] The preparation of the stand-by slurry in step (1) of Example 1 is adjusted as follows: 0.5% by mass of HPMC and 10% by mass of water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 10 hours, 0.5% of PC67 is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 hours, aggregate (68% quartz, 8% atomization core waste, 4% talcum powder) and 5% feldspar are added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 10 hours to obtain a fourth mixed solution, 4% walnut sand is added to the fourth mixed solution, and the ball-milling is continued for 2 hours to obtain a stand-by slurry.
[0098] Example 5
[0099] Similar to Example 1, except that:
[0100] The preparation of the stand-by slurry in step (1) of Example 1 is adjusted as follows: 2% by mass of PVA, 0.5% by mass of CMC, and 25% by mass of water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 15 hours, aggregate (51% quartz, 6% atomization core waste, 3% talcum powder) is added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 10 hours to obtain a fourth mixed solution, 12.5% of graphite is added to the fourth mixed solution, and the ball-milling is continued for 2 hours to obtain the stand-by slurry.
[0101] Example 6
[0102] Similar to Example 1, except that:
[0103] The preparation of the stand-by slurry in step (1) of Example 1 is adjusted as follows: 1.5% PVA by mass and 16% water by mass are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 15 hours, 0.5% PC67 is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 hours, aggregate (51% quartz, 6% atomization core waste, 3% talcum powder) and 2% glass powder are added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 10 hours to obtain a fourth mixed solution, 20% PMMA is added to the fourth mixed solution and ball-milled for 2 hours to obtain a stand-by slurry.
[0104] Comparative Example 1
[0105] Similar to Example 1, except that:
[0106] The preparation of the stand-by slurry in step (1) of Example 1 is adjusted as follows: 1% by mass of PVA, 0.1% by mass of CMC and 15% by mass of water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 15 hours, 0.5% of PC67 is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 hours, aggregate (60% atomization core waste, 18% talcum powder) and 2% glass powder are added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 0 hours to obtain a fourth mixed solution, 3.4% PMMA is added to the fourth mixed solution and ball-milled for 2 hours to obtain a stand-by slurry.
[0107] The above Examples 1 to 6 and Comparative Example 1 were subjected to performance tests and observations to obtain Table 1.
[0108] Test method:
[0109] 1. Particle size test method
[0110] The particle size of the wax removal powders of Examples 1 to 6 and Comparative Example 1 was tested using a laser particle size analyzer.
[0111] 2. Viscosity test method
[0112] The viscosity of the wax removal powders of Examples 1 to 6 and Comparative Example 1 was tested by a viscometer.
[0113] 3. Powder fluidity test method
[0114] The fluidity test of the wax removal powders of Examples 1 to 6 and Comparative Example 1 was carried out using a flow rate cup.
[0115]
[0116]
[0117] Reference Figure 3, is the size change of the porous ceramic substrates of Example 1 and Comparative Example 1 as the wax removal powder is used more times. It can be seen that the size fluctuation of the porous ceramic substrate of Example 1 is lower than that of Comparative Example 1 as the wax removal powder is used more times.
[0118] In one embodiment of the present application, during the preparation of the porous ceramic matrix, a green body for preparing the porous ceramic matrix is placed in a mold, and the green body is buried in wax removal powder for a wax removal process. In order to achieve a better wax removal effect, wax removal is usually performed multiple times to remove paraffin, beeswax, stearic acid, pore-forming agent, glass powder and other substances in the green body. The aggregate of the wax removal powder of the present application contains quartz powder, which is a high silicon content material with high inertness. It can avoid the reaction of the wax removal powder with the porous ceramic matrix to form a eutectic, reduce the problem of wax removal and powder sticking, and in multiple wax removals, the size of the porous ceramic matrix can be kept basically consistent. The porous ceramic matrix of Example 1 has smaller size fluctuations than the porous ceramic matrix of Comparative Example 1.
[0119] Reference Figure 4 and Figure 5 , Figure 4 This is the porous ceramic substrate of Example 1 after using the wax removal powder. Figure 5 This is the case of the porous ceramic substrate in Comparative Example 1 after using the wax removal powder. It can be seen that Figure 4 The medium porous ceramic substrate uses the wax removal powder provided in Example 1, and the surface white spots of the porous ceramic substrate are less; Figure 5 The medium porous ceramic substrate uses the wax removal powder provided in Comparative Example 1. The porous ceramic substrate has many white spots on its surface. This is because some wax removal powder remains and some wax removal powder reacts with the porous ceramic substrate to form a eutectic.
[0120] It can be seen from the relevant data in Table 1 that the wax removal powders of Examples 1 to 6 all use quartz-containing aggregates in the formula, the viscosity and powder fluidity of the wax removal powders of Examples 1 to 6 are lower than those of Comparative Example 1, the high temperature resistance temperature is higher than that of Comparative Example 1, and the wax removal effect of the wax removal powder is also better than that of Comparative Example 1. The wax removal powder prepared using the formula of the present application has a high silicon content and high inertness, which can reduce the reaction between the wax removal powder and the porous ceramic matrix, thereby reducing the problem of wax removal and powder sticking.
[0121] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A wax removal powder, characterized in that: The raw materials for preparing the wax removal powder include: Aggregate, with a mass percentage of greater than or equal to 60% and less than or equal to 80%; the aggregate comprises quartz powder; Inorganic binder, mass percentage greater than 0 and less than or equal to 5%; Organic binder, mass percentage greater than or equal to 0.5% and less than or equal to 2%; Pore-forming agent, the mass percentage is greater than 0 and less than or equal to 20%; Dispersant, mass percentage greater than 0 and less than or equal to 0.5%; Suspension agent, mass percentage greater than 0 and less than or equal to 0.5%; Water, mass percentage greater than or equal to 10% and less than or equal to 25%.
2. The wax removal powder according to claim 1, characterized in that: The aggregate further comprises atomizer core waste and / or talc.
3. The wax removal powder as claimed in claim 2, characterized in that: The mass percentage of the quartz powder in the aggregate is greater than or equal to 70% and less than or equal to 85%, the mass percentage of the atomization core waste in the aggregate is greater than or equal to 10% and less than or equal to 20%, and the mass percentage of the talc in the aggregate is greater than or equal to 5% and less than or equal to 10%.
4. The wax-removing powder according to claim 3, characterized in that: The mass percentage of SiO2 in the quartz powder is greater than or equal to 97% and less than 100%; the mass percentage of SiO2 in the atomization core waste is greater than or equal to 80% and less than or equal to 90%; the mass percentage of SiO2 in the talc is greater than or equal to 60% and less than or equal to 65%.
5. The wax removal powder according to claim 1, characterized in that: The median particle size of the aggregate is in the range of 10 μm to 20 μm.
6. The wax removal powder according to claim 1, characterized in that: The inorganic binder includes glass powder and / or feldspar.
7. The wax-removing powder according to claim 1, characterized in that: The inorganic binder at least includes potassium oxide and sodium oxide, and the mass fraction of the potassium oxide and the sodium oxide in the wax removal powder is less than or equal to 1%.
8. The wax-removing powder according to claim 1, characterized in that: The median particle size of the inorganic binder is in the range of 1 μm to 5 μm.
9. The wax-removing powder according to claim 7, characterized in that: The softening point temperature of the inorganic binder is 1200°C to 1250°C.
10. The wax-removing powder according to claim 1, characterized in that: The mesh number of the sieve used for sieving the wax removal powder ranges from 80 meshes to 200 meshes.
11. The wax-removing powder according to claim 1, characterized in that: The organic binder includes polyvinyl alcohol and / or hydroxypropyl methylcellulose; The pore-forming agent comprises at least one of polymethyl methacrylate, graphite powder and walnut sand; the median particle size of the pore-forming agent ranges from 1 μm to 10 μm; The dispersant includes at least one of sodium humate, PC67 and polyacrylic acid amine; The suspending agent includes carboxymethyl cellulose.
12. The wax-removing powder according to any one of claims 1 to 11, characterized in that: The porosity of the wax-removing powder is 30% to 50%.
13. The wax-removing powder according to any one of claims 1 to 11, characterized in that: In the wax removal powder, the mass fraction of SiO2 is greater than or equal to 85% and less than or equal to 98%.
14. A method for preparing wax removal powder, characterized in that: Used to prepare the wax removal powder according to any one of claims 1 to 13, comprising: Prepare the slurry to be used by using the raw materials for preparing the wax removal powder; Performing spray granulation on the slurry to be used to obtain a first intermediate product; Screening the first intermediate product once to obtain a second intermediate product; calcining the second intermediate product to obtain a third intermediate product; The third intermediate product is subjected to secondary screening to obtain the wax removal powder.
15. The method for preparing wax-removing powder according to claim 14, characterized in that: The preparation of the slurry to be used comprises: An organic binder, a suspending agent and water are mixed to obtain a first mixed solution, and after stirring the first mixed solution for 10 to 15 hours, a dispersant is added to obtain a second mixed solution, and after stirring the second mixed solution for 5 to 7 hours, aggregates and inorganic binders are added to obtain a third mixed solution, the third mixed solution is added to a ball mill and ball-milled for 5 to 10 hours to obtain a fourth mixed solution, a pore-forming agent is added to the fourth mixed solution and ball-milled for 2 to 4 hours to obtain the stand-by slurry.
16. The method for preparing wax-removing powder according to claim 14, characterized in that: The step of spraying and granulating the slurry to be used to obtain the first intermediate product comprises: The slurry to be used is placed in a centrifugal spray tower, the inlet air temperature of the centrifugal spray tower is 210°C to 220°C, the outlet temperature is 100°C to 110°C, the feed frequency is 25Hz to 30Hz, and the centrifugal speed is 20Hz to 30Hz.
17. The method for preparing wax-removing powder according to claim 14, characterized in that: The step of screening the first intermediate product once to obtain the second intermediate product comprises: Using a screening machine to screen the first intermediate product to obtain a second intermediate product; The mesh number range of the sieve used for sieving the second intermediate product is 60 mesh to 200 mesh.
18. The method for preparing wax-removing powder according to claim 14, characterized in that: In the step of calcining the second intermediate product to obtain the third intermediate product, the calcination temperature is 1250°C to 1350°C.
19. The method for preparing wax-removing powder according to claim 14, characterized in that: The step of performing secondary screening on the third intermediate product to obtain the wax removal powder comprises: screening the third intermediate product using a screening machine to obtain the wax removal powder; The mesh number of the sieve used for sieving the wax removal powder ranges from 80 meshes to 200 meshes.
Citation Information
Patent Citations
Wax repulsed powder, and production method
CN101003437A
Composition and porous ceramic atomization core containing continuous glass phase
CN113149697A
Composition and anti-leakage oil layer and atomizing core thereof
CN114315419A
Dewaxing method for ceramic hot die-casting forming
CN117140687A
Porous ceramic with gradient pore structure and preparation method thereof
CN117720339A